2022
DOI: 10.1186/s13034-022-00492-9
|View full text |Cite
|
Sign up to set email alerts
|

Depression and suicidal behavior among adolescents living with HIV in Botswana: a cross-sectional study

Abstract: Background Depression and suicidal behavior are the main causes of disability and morbidity, especially in adolescents living with HIV (ALWHIV). Data regarding these are lacking in Botswana, a country with a predominantly youthful population and ranked among the top four in the world most affected by HIV. Therefore, the present study aimed to estimate the prevalence of depression and suicidal behavior and explore their associated factors in Botswana ALWHIV. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Correspondingly, most research has focused on Eastern and Southern Africa. A cross-sectional study in Botswana, which ranked among the top four countries most affected by HIV, reported the prevalence of depression among adolescents living with HIV were 23% ( Olashore et al, 2022 ), which is consistent with the rate (24–27%) in the systematic review in sub-Saharan ( Dessauvagie et al, 2020 ). West et al (2019) found that the majority of HIV-infected adolescents were infected perinatally, and the adolescents who receive earlier and higher social support were less likely to have mental health symptoms ( West et al, 2019 ).…”
Section: Discussionsupporting
confidence: 70%
“…Correspondingly, most research has focused on Eastern and Southern Africa. A cross-sectional study in Botswana, which ranked among the top four countries most affected by HIV, reported the prevalence of depression among adolescents living with HIV were 23% ( Olashore et al, 2022 ), which is consistent with the rate (24–27%) in the systematic review in sub-Saharan ( Dessauvagie et al, 2020 ). West et al (2019) found that the majority of HIV-infected adolescents were infected perinatally, and the adolescents who receive earlier and higher social support were less likely to have mental health symptoms ( West et al, 2019 ).…”
Section: Discussionsupporting
confidence: 70%
“…There were three main responses: ‘still struggling,’ ‘has accepted status,’ and ‘do not know my status.’ However, the last response was excluded from the analysis. A more detailed description of this has been reported in a previous manuscript [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…This was a randomized, controlled trial to assess the psychological intervention program in ALWHIV, aged 15–19, who attend medical clinics at Botswana Baylor Children's Clinical Centre of Excellence (BBCCCE). An earlier manuscript has reported details regarding the study site and clinic activities [ 17 ].…”
Section: Methodsmentioning
confidence: 99%